Merger & acquisition strategy for growth, improved performance and survival in the financial sector - Farhan Ahmed; Aneeta Manwani; Shafique Ahmed (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2018)
This paper aims to provide comparative information on mergers & acquisition activities in the banking sector of Pakistan. This study used accounting ratios to analyze the financial performance of banks in Pakistan after merger and acquisitions. The study utilized secondary data which were taken from Thomson Financial Services Worldwide M&A database, financial statements of bank’s corporate website and Pakistan stock exchange. In this study, financials for eleven years (2005-2016) were analyzed by using ratios. In spite of certain limitations, accounting ratios are still reflected as an easy and reliable analytical tool. Ratio analysis, being a time-tested method, is most frequently employed in all financial decision-making processes. The results show that the financial performance of banking sector of Pakistan in the capacities of profitability, and leverage, has been quite satisfactory before the merger deal. It means that merger deal fails to improve the financial performance of the bank, and banks merge with other small or equal size banks only to capture market share, to open Islamic window, for cost-cutting, to create synergy, to gain efficient resources and to unlock hidden values